Reflection on EFL/ESL Teachers' Emotional Creativity and Students L2 Engagement - Sun, Xianyi; Li, Jiao; Meng, Lan (Frontiers in Psychology, 2021)
Emotions are one of the pillars of all human beings which can play a vital role in providing education. Emotions can affect all aspects of education. The feeling of creativity is one of the subsets of emotions. This feeling strongly affects the performance of education and the level of involvement of students. Student involvement has different aspects: social aspect; individual aspect, and emotional aspect. The present review shows that the emotional aspect of L2 engagement plays a pivotal role in the process of learning the language in English as a foreign language (EFL) and English as a second language (ESL) context. In dealing with the emotional aspect of teachers, the personal, social, and environmental aspects of the individual should be considered. The paper concludes with some pedagogical implications and provides some suggestions for future research.